Auditory Performances in Older and Younger Adult Cochlear Implant Recipients: Use of the HEARRING Registry. Issue 8 (September 2019) - Hofkens-Van den Brandt, Anouk; Mertens, Griet; Gilles, Annick; Fransen, Erik; Lassaletta, Luis; Gavilan, Javier; Calvino, Miryam; Yanov, Yuri; Kuzovkov, Vladislav; Kliachko, Dmitrii; Zernotti, Mario; Gregorio, Dra Maria Fernanda Di; et al.
Abstract : Objective: To evaluate the hearing outcomes of cochlear implantation in different age groups by using data collected in the HEARRING registry. Methods: A multicenter study. Data of 146 patients were collected in a HEARRING registry. Patients were divided into three different age groups; ⩽ 55 years old (age group 1, n = 66), 56 to 69 years old (age group 2, n = 45), and ≥ 70 years old (age group 3, n = 35). Speech in quiet (SPIQ), speech in noise (SPIN), and hearing implant sound quality index (HISQUI19) scores were evaluated for the different age groups at different test moments (preoperatively, 3, 6, 12, and 24 mo after first fitting). Results: A statistically significant difference ( p < 0.01) was found between preoperative scores and the scores on all the follow-up moments across all age groups. For SPIQ and SPIN, none of the time points showed a statistically significant age effect ( p = 0.88 and p = 0.89). For HISQUI19 scores, a statistically significant age effect was found at 12 months after first fitting. The oldest age group scored significantly lower on the HISQUI19 compared with the youngest age group. Conclusion: Hearing outcomes of adult cochlear implant users of different age groups were evaluated. The SPIQ and SPIN tests showed no significant differences between the different age groups. Nevertheless, the youngest group scored significantly better on self -perceived benefit (HISQUI19) with a cochlear implant compared with the oldest age group. Further research is needed to receive more insight into cochlear implantation in the elderly and its implications on rehabilitating and supporting this expanding older population.